2009
DOI: 10.1002/jclp.20544
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the transcendental meditation program on mindfulness

Abstract: Mindfulness is associated with low levels of neuroticism, anxiety, and depressive symptoms, as well as high levels of self-esteem and satisfaction with life (Brown & Ryan, 2003). As part of a 3-month randomized waitlist-controlled trial of the effects of the Transcendental Meditation (TM) program on university students (N=295), we examined the impact of TM practice on mindfulness as measured by the Kentucky Inventory of Mindfulness Skills (KIMS; Baer, Smith, & Allen, 2004). A repeated measures ANOVA on total K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 28 publications
2
33
1
Order By: Relevance
“…We did not expect and we did not find the degree of difference that has been reported with mindfulness or meditation training populations (Tanner, et al, 2009). Comparisons across studies may be problematic in a number of ways (Quickel, Johnson, & David, 2014).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…We did not expect and we did not find the degree of difference that has been reported with mindfulness or meditation training populations (Tanner, et al, 2009). Comparisons across studies may be problematic in a number of ways (Quickel, Johnson, & David, 2014).…”
Section: Discussionmentioning
confidence: 53%
“…Our results are consistent with studies that have compared and examined the process of meditation on mindfulness. Tanner, et al (2009) examined the effects of Transcendental Meditation (TM) on mindfulness scores using the KIMS. At the start, Tanner et al's Wait List group (M = 128.03) and TM start group (M = 127.48) were not significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…26 Similarly, Tanner et al and Joseffson et al have also reported significant change in FFMQ "Describe" sub scale. 27,28 Resilience is best defined as successful adaptation to adverse circumstances. In general, the concept of resilience reflects desire for great optimism under adversity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the effects of TM in college students on mindfulness (Aldahadha, 2013;Tanner et al, 2009), stress, anxiety (Dillbeck, 1977), and depression (Burns et al, 2011) show significant positive results. One longitudinal study examined the effect of practicing TM on nonverbal intelligence scores (Fergusson, Bonshek, & Masson, 1995) in Cambodian undergraduate students.…”
Section: Mindfulness Meditation and Tmmentioning
confidence: 99%
“…In addition, anxiety may be greater due to the changing nature of college students' schedule. Research shows that distress can be decreased in college student populations through the practice of TM (Burns et al, 2011) and that significant differences in Brain Integration Scale scores (frontal coherence, alpha/beta absolute power ratios, timing/magnitude of brain preparatory responses) and sleepiness were seen after 10 weeks of TM practice (Travis et al, 2009). The Brain Integration Scale was created by Frederick Travis after results showed "changes in brain patterns during challenging cognitive tasks after the meditation session" (Travis et al, 2009).…”
Section: Mindfulness Meditation and Tmmentioning
confidence: 99%